Recent Technology Developments in Biogas Production from Waste Materials in Malaysia - Mohd Johari, S.A. (John Wiley and Sons Inc, 2021)
Solid waste management towards the sustainable process is one of the major undertakings of the Malaysia Solid Waste Management Department. Hence, development towards biofuels including biogas production from wastes has been escalating in Malaysia. There have been some major innovations in biogas production, including design and operation of the reactor, the presence of an additive, change in mixing regime, supporting unit, measurement, and monitoring systems, since the technology has developed. The sections mainly included are types of digesters, strategies such as upstream, mainstream, and downstream. In upstream strategies, the hydrothermal pretreatment of anaerobic digestion showed a higher improvement of biogas by an increase of 222 of methane content. The mainstream strategies showed that co-digestion wasÂ the best method to increase the methane yield to 305â445 mL gâ1 VS. In downstream system, methane content can be upgraded from 60 to 90 by applying water scrubber. This paper aims to discuss the recent trends and innovations in biogas production from waste and their pathways in details. Â© 2021 Wiley-VCH GmbH